Optimism, Spousal Support and Quality Of Life in Women with Breast Cancer - Maryum Khalid, Saima Majeed, (Pakistan Journal of Medical & Health Sciences, 2022)
Breast cancer is the 2nd most common cancer among women. Aim: To determine the level of optimism and spousal support in women with breast cancer. Study Design: Cross sectional study. Methodology: Data was collected using the purposive sampling technique from oncology departments of two public hospitals. Measures for data collection consisted of a demographic information sheet, and three scales including LOT-R (Ay,2009), DCI (Shuja et. al., 2020) and WHO-QOL BREF scale (Saqib,2017). A total of 80 women with a mean age of 35(SD=6.95) participated in the research. Statistical analysis: The collected data was analyzed by using SPSS version 25. Chi square ware applied with P-value< 0.05 as significant. Results: Correlation revealed that optimism had a significant positive relationship with negative dyadic coping and with QOL scales except for Physical Health. All the subscales of DCI had a significant relationship with the subscales of QOL. It was found through HLM that education, socioeconomic status, cancer stage, monthly income, professional status after illness and optimism made a statistically significant contribution. Conclusion: It was concluded that optimism, negative dyadic coping and quality of life has a significant relationship. Likewise, education, socioeconomic status, cancer stage, monthly income, professional status after illness and optimism were found to be the determining factors of quality of life.